PARTIKEL KASUS NI DALAM BAHASA JEPANG - Rosliana, Lina (KIRYOKU, 2017)
Particles are one of the Japanese part of speech that can not stand alone in a sentence and have no conjugation. Particles must be attached with other elements in the sentence to be able to know its meaning. In practice, however, the meaning of a particle often resembles the meaning of other particles. This is what makes Japanese learners often have difficulty. In this research, we will discuss the particle case ni, one particle that has many similarities with other particle.